Neratinib after trastuzumab-based adjuvant therapy in patients from Asia with early stage HER2-positive breast cancer - Iwata, Hiroji; Masuda, Norikazu; Kim, Sung-Bae; Inoue, Kenichi; Rai, Yoshiaki; Fujita, Takashi; Chiu, Joanne; Ohtani, Shoichiro; Takahashi, Masato; Miyaki, Toshiko; Lu, Yen-Shen; Xu, Binghe; et al. (Future Medicine, 2019)
Aim: To evaluate the efficacy and safety of neratinib as extended adjuvant therapy in patients from Asia based on exploratory analyses of the Phase III ExteNET trial. Patients & methods: A total of 2840 women with early stage HER2-positive breast cancer were randomly assigned to neratinib 240 mg/day or placebo for 1 year after trastuzumab-based adjuvant therapy. Results: A total of 341 patients were from Asia (neratinib, n = 165; placebo, n = 176). 2-year invasive disease-free survival rates were 92.8 and 90.8% with neratinib and placebo, respectively (HR: 0.70; 95% CI: 0.31-1.55), and 5-year rates were 91.9 and 87.2%, respectively (HR: 0.57; 95% CI: 0.27-1.13). Diarrhea was the most common adverse event with neratinib. Conclusion: Extended adjuvant therapy with neratinib reduces disease recurrences in Asian women with HER2-positive breast cancer. Trial registration: Clinicaltrials.gov NCT00878709. © 2019 Future Medicine Ltd.